Structural and functional features of phytoene synthase isoforms PSY1 and PSY2 in pepper Capsicum annuum L. cultivars - E. A. Dyachenko; M. A. Filyushin; G. I. Efremov; E. A. Dzhos; A. V. Shchennikova; E. Z. Kochieva (Вавиловский журнал генетики и селекции)
The fruits of various pepper cultivars are characterized by a different colour, which is determined by the pigment ratio; carotenoids dominate in ripe fruits, while chlorophylls, in immature fruits. A key regulator of carotenoid biosynthesis is the phytoene synthase encoded by the PSY gene. The Capsicum annuum genome contains two isoforms of this enzyme, localized in leaf (PSY2) and fruit (PSY1) plastids. In this work, the complete PSY1 and PSY2 genes were identified in nine C. annuum cultivars, which differ in ripe fruit colour. PSY1 and PSY2 sequence variability was 2.43 % (69 SNPs) and 1.21 % (36 SNPs). The most variable were PSY1 proteins of the cultivars ‘Maria’ (red-fruited) and ‘Sladkij shokolad’ (red-brown-fruited). All identified PSY1 and PSY2 homologs contained the phytoene synthase domain HH-IPPS and the transit peptide. In the PSY1 and PSY2 HH-IPPS domains, functionally significant sites were determined. For all accessions studied, the active sites (YAKTF and RAYV), aspartate-rich substrate-Mg2+-binding sites (DELVD and DVGED), and other functional residues were shown to be conserved. Transit peptides were more variable, and their similarity in the PSY1 and PSY2 proteins did not exceed 78.68 %. According to the biochemical data obtained, the largest amounts of chlorophylls and carotenoids across the cultivars studied were detected in immature and ripe fruits of the cv. ‘Sladkij shokolad’ and ‘Shokoladnyj’. Also, ripe fruits of the cv. ‘Nesozrevayuschij’ (green-fruited) were marked by significant chlorophyll content, but a minimum of carotenoids. The PSY1 and PSY2 expression patterns were determined in the fruit pericarp at three ripening stages in ‘Zheltyj buket’, ‘Sladkij shokolad’, ‘Karmin’ and ‘Nesozrevayuschij’, which have different ripe fruit colours: yellow, red-brown, dark red and green, respectively. In the leaves of the cultivars studied, PSY1 expression levels varied significantly. All cultivars were characterized by increased PSY1 transcription as the fruit ripened; the maximum transcription level was found in the ripe fruit of ‘Sladkij shokolad’, and the lowest, in ‘Nesozrevayuschij’. PSY2 transcripts were detected not only in the leaves and immature fruits, but also in ripe fruits. Assessment of a possible correlation of PSY1 and PSY2 transcription with carotenoid and chlorophyll content revealed a direct relationship between PSY1 expression level and carotenoid pigmentation during fruit ripening. It has been suggested that the absence of a typical pericarp pigmentation pattern in ‘Nesozrevayuschij’ may be associated with impaired chromoplast formation.